Preferences for models of peer support in the digital era: A cross‐sectional survey of people with cancer. Issue 9 (29th June 2018) - Boyes, Allison; Turon, Heidi; Hall, Alix; Watson, Rochelle; Proietto, Anthony; Sanson‐Fisher, Robert
Abstract: Objective: Many people with cancer report an unmet need for peer support, yet participation rates are low. This study examined cancer patients' preferences for participating in peer support, and the characteristics associated with having or wanting to participate in peer support. Methods: Adult cancer patients were recruited from outpatient oncology clinics at 5 hospitals in Australia. Participants were invited to self‐complete 2 questionnaires: one at recruitment assessing their demographic and cancer characteristics, and another 4 weeks later assessing their preferences for participating in cancer‐related peer support. Results: The peer support questionnaire was completed by 177/273 (65%) of participants. Most (59%, n  = 104) had or wanted to participate in peer support. More than half reported that it was important the people they connected with had the same cancer treatment (56%, n  = 99) or type of cancer (53%, n  = 94) as themselves. Half had or wanted to participate in 1‐to‐1 peer support (52%, n  = 92). Half had or wanted to connect with peers face‐to‐face (53%, n  = 93). Only 13% ( n  = 23) were receptive to connecting with peers over the internet. Being aged ≤65 years was significantly associated (OR = 2.3; 95% CI: 1.1‐5.1) with reporting a preference for participating in peer support. Conclusions: Cancer patients are interested in participating in peer support, particularly those who are younger. Despite the digital era, traditional forms of peer support continue to be important in supporting people with cancer. Greater understanding of the barriers to cancer patients' involvement in potentially low cost and high reach web‐based models of peer support is required.